Fracture of neck of femur with fracture of posterior column of acetabulum: a rare case of floating hip - Neogi, Avik K.; Kumar, Naresh; Das, Jyotirmay; Lamba, Akshay; Garg, Abhishek; Kundu, Ankush; Yadav, Pritam; Sachdeva, Sachin; Malik, Ipanshu; Khare, Neeraj (International Journal of Research in Orthopaedics, 2020)
Injuries around the hip joint are one of the most common orthopedic injuries and these types of injuries are grossly debilitating until treated properly. Simultaneous occurrence of fracture of proximal femur with fracture of ipsilateral acetabulum or pelvis is termed as floating hip injury. These injuries are very rare, only to be found 1 in 10,000 as well as there is lack of literature support regarding proper treatment protocol. Here we are going to present a case of fracture of neck of left femur along with fracture of left acetabulum in a 45 years old male undergone road traffic accident.